Neuropsychiatric disorders in chronic hepatitis C patients after receiving interferon or direct-acting antivirals: a nationwide cohort study - Fang, Yu; Chen, Chung-Yu; Yu, Hsien-Chung; Lin, Pei-Chin (Frontiers in Pharmacology, 2023)
Background: Data on the neuropsychological outcomes after receiving direct-acting antivirals (DAAs) among chronic hepatitis C (CHC) patients have not been well-documented. Aim: This study aimed to evaluate the difference in incidence of neuropsychological disorders (NPDs) after treatment completion between CHC patients receiving interferon (IFN) therapy and DAA therapy. Methods: A nationwide retrospective cohort study was performed using Taiwan’s National Health Insurance Research Database (NHIRD) between 2010 and 2018. CHC patients without pre-existing mental disorders were included and divided into the treatment (Tx)-naïve DAA group, retreatment (re-Tx) DAA group, and Tx-naïve IFN group based on their HCV therapy. Propensity score matching was used to balance baseline differences between groups. The primary outcome was the incidence of NPDs during 6 months after completion of therapy. Results: After one-to-one matching, there were 6,461 pairs of patients selected from the Tx-naïve DAA group and Tx-naïve IFN group and 3,792 pairs from the re-Tx DAA group and Tx-naïve IFN group. A lower incidence of NPDs was observed in the Tx-naïve DAA group than in the Tx-naïve IFN group (HR = 0.72, 95% CI = 0.55–0.94, and p = 0.017). The risk of NPDs did not differ between the re-Tx DAA group and the Tx-naïve IFN group (HR = 0.74, 95% CI: 0.52–1.05, and p = 0.092). Conclusion: DAA therapy was associated with lower risk of NPDs when compared with IFN therapy among Tx-naïve CHC patients in a 6-month period after treatment completion, especially among the patients less than 65 years, male gender, and cirrhosis.